Teknologi dan Dominasi atas Alam Kritik Paus Fransiskus dan Heidegger terhadap Paradigma Teknokratis atas Alam - Yulius Suroso (P3TK, Sanata Dharma University, 2021)
What Pope Francis said about environment crisis, then confirms what Heidegger had long thought. The paradigm, which Heidegger calls “framing” (gestell), then penetrates the world of politico-economy, so that the economy accepts any technological advances that bring benefits, regardless of the possible negative impact on humans and other creatures. In a profit mindset, there is no room for thinking about natural rhythms, phases of withering and regeneration, or about the complexity of ecosystems. Nature is only thought as an economic resource. To overcome this, humans need to be educated. Humans need to be aware that humans exist in a reciprocal relationship with nature. Human existence is not a separate thing from nature but exists in the same ecosystem. Furthermore, humans need to realize that participatory action to pay attention to nature is fundamentally compatible with cultivating a relationship with God. Panentheism encourages humans to respect creation, because in creation, God is not only present, but also continues to work in it.